Effect of Baihe Gujin decoction combined with Shengmai powder on the expression of IL-1β and IL-1Ra in peripheral blood CD14+ monocytes from patients with pulmonary tuberculosis: Baihe Gujin with Shengmai effects on IL-1β, IL-1Ra - Wang, Ke; Li, Lin; Wang, Yanqiu; Fang, Guoyan; Wei, Ming; Ding, Han; Liu, Wei; Huang, Zhenghui (Cellular and Molecular Biology, 2022)
This experiment was conducted to investigate the effect of taking Baihe Gujin decoction combined with Shengmai powder on IL-1β and IL-1Ra expression in peripheral blood CD14+ monocytes from patients with pulmonary tuberculosis. For this purpose, one hundred adult patients with primary pulmonary tuberculosis were selected for the study. The age of the enrolled cases ranged from 18 to 60 years old, with a controlled male to the female sex ratio of about 1:1. The Chinese medical evidence was considered to be a qi-yin deficiency type of pulmonary consumption. The patients were randomly divided into experimental and control groups, 50 cases each. In addition, 50 cases of healthy people were selected as a healthy control group, totaling 150 cases. In the experimental group, patients were given Baihe gujin decoction and Shengmai powder based on conventional western medicine, 1 dose for 1 day, 150mL/time for 2 times. The control group was treated with conventional Western medicine. 2 mL of fasting elbow venous blood from the subjects was taken in the morning. Peripheral blood mononuclear cells were isolated by density centrifugation. Monocytes were obtained after incubation with 5 μL of CD14+ immune magnetic beads at 4°C. The relative expression of IL1β and IL1R genes were measured using real-time quantitative PCR (RT-PCR), respectively. Results showed that the relative expression of IL1β and IL1R genes was significantly lower in the experimental group after 3 months compared with the control group, and the statistical difference was highly significant (p<0.01). It was concluded that the administration of Baihe gujin decoction and Shengmai powder was closely related to the relative expression of IL1β and IL1R genes in patients' serum, indicating that Baihe gujin decoction and Shengmai powder have an important role in improving the clinical symptoms of pulmonary tuberculosis.